THE STRUCTURE OF THE SOUTH URALS FORELAND FOLD AND THRUST BELT AT THE TRANSITION TO THE PRECASPIAN BASIN - Brown D.; Alvarez-Marron J.; Perez-Estaun A.; Gorozhanina Y.; Puchkov V. (My University, 2004)
The structural architecture of the south Urals foreland fold and thrust belt at the transition into the Precaspian Basin is that of a wedge-shaped, west-vergent thrust stack with a significant amount of basement involvement. The surface geology of this part of the thrust belt is dominated by the south Urals accretionary complex, whose internal structure was primarily developed during Late Devonian to Early Carboniferous arc-continent collision and which was subsequently incorporated into the thrust belt. A number of thrusts, identified in the field and in seismic profiles, breach the accretionary complex, suggesting that they post-date its emplacement and may be related to the development of the foreland fold and thrust belt. A basal detachment can be confidently defined only beneath the frontal part of the thrust belt, making it difficult to construct balanced and restored cross-sections and therefore to calculate the amount of shortening. Nevertheless, the amount of shortening appears to be of the order of only a few tens of kilometres. There is a major change in the structural style along the frontal part of the thrust belt that may be related to basement topography and/or basement response to the deformation across a basement fault oriented at a high angle to the structural grain of the thrust belt.
Keywords: Urals; structural geology